2021
DOI: 10.1111/ecc.13523
|View full text |Cite
|
Sign up to set email alerts
|

Avoidant coping as mediator of the relationship between rumination and mental health among family caregivers of Chinese breast cancer patients

Abstract: Introduction: Family caregivers of cancer patients were often referred to the 'forgotten patients', yet little researches have been conducted on their mental health. Rumination might put family caregivers at risk for psychological distress during the caregiving, such as stress and anxiety. The aim of the present study was to explore the relationship between rumination, stress and anxiety among family caregivers of breast cancer patients in China and examine the mediating role of avoidant coping in this relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…For further explanation, Yuanyuan and Chen (2021) agreed this result through their study for how rumination predicted ineffective coping and stress. They mentioned that caregivers with ideas such as catastrophic appraisals and worrying thoughts regarding burden, their maladaptive metacognitive thoughts or behaviors could increase.…”
Section: Mediation Analysissupporting
confidence: 62%
“…For further explanation, Yuanyuan and Chen (2021) agreed this result through their study for how rumination predicted ineffective coping and stress. They mentioned that caregivers with ideas such as catastrophic appraisals and worrying thoughts regarding burden, their maladaptive metacognitive thoughts or behaviors could increase.…”
Section: Mediation Analysissupporting
confidence: 62%
“…Our research identified rumination as a significant mediating factor between stress, depression, and caregiver burden. Rumination, or the persistent dwelling on distressing thoughts, can amplify the impact of stress and depression on caregiver burden, under-lining the vital role of psychological factors and coping strategies in managing caregiver burden [39].…”
Section: Discussionmentioning
confidence: 99%
“…This distress can further compound caregiver burden. Moreover, rumination often encourages avoidant coping strategies, representing a risk factor for higher stress and anxiety levels [39].…”
Section: Discussionmentioning
confidence: 99%
“…According to Response Style Theory (RST), rumination enhances maladaptive coping and dysfunctional attitudes, which impair problem-solving and intensify emotional distress (Nolen-Hoeksema et al, 2008). Similar to the perspective of RST, in the literature it is evident that individuals with cancer are prone to focus on intrusive ruminations (Öcalan & Üzar-Özçetin, 2021;Renna et al, 2021;Tan et al, 2021). This subsequently leads to catastrophic cognitions (e.g., "What did I do to deserve this?…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, deliberate rumination aids individuals in understanding the distress that they are experiencing (Kamijo & Yukawa, 2018). As a result, it has greater value in shaping the consequences (Tan et al, 2021). According to Response Style Theory (RST), rumination enhances maladaptive coping and dysfunctional attitudes, which impair problem‐solving and intensify emotional distress (Nolen‐Hoeksema et al, 2008).…”
Section: Introductionmentioning
confidence: 99%